Case of bullous pemphigoid refractory to corticosteroids by antiepileptic drug‐induced CYP3A4 - Asakawa, Riko; Ogawa, Youichi; Maejima, Eri; Honobe‐Tabuchi, Akiko; Okamoto, Takashi; Mitsui, Hiroshi; Kagawa, Yoshiyuki; Shimada, Shinji; Kawamura, Tatsuyoshi (Journal of dermatology, 2023)
The most common treatment option for patients with bullous pemphigoid is systemic corticosteroids. CYP3A4, a drug‐metabolizing enzyme in the liver, metabolizes synthetic steroids to a varying degree. Although there are many CYP3A4‐inducing drugs, several antiepileptic drugs, such as phenytoin and phenobarbital, strongly induce CYP3A4, thereby reducing the effects of corticosteroids. Here, we report a case of refractory bullous pemphigoid that rapidly improved after the discontinuation of phenytoin and phenobarbital. To achieve adequate pharmacological effects of corticosteroids, we must always ensure that patients who require corticosteroids for treatment are not medicated with CYP3A4‐inducing agents.